Factors Affecting Firm Value and the Economic Significance of Firm Size as a Moderator: A Study of the Industrial Sector on the IDX (2020–2023) - Sianipar, Tiurma Santi Angelina; Ginting, Fitri Andriani; Barus, Andreani Caroline (International Journal of Economics Development Research (IJEDR), 2025)
This study investigates the influence of tax planning, profitability, liquidity, capital structure, and firm growth on firm value, with firm size as a moderating variable, in industrial sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Using a quantitative descriptive approach, the study analyzes 75 firm-year observations from 15 purposively selected companies. Firm value is proxied by Price to Book Value (PBV), while other variables are measured using standard financial ratios. Data were analyzed using multiple linear regression and moderation analysis with the absolute difference value method. The findings indicate that profitability, capital structure, and firm growth significantly influence firm value, with profitability being the most dominant factor. Firm size strengthens the relationship between key financial indicators and firm value, highlighting the advantage of scale in attracting investor confidence. The study emphasizes the importance of strong financial fundamentals, especially in navigating external shocks such as the COVID-19 pandemic. Recommendations are provided for companies, investors, regulators, and future researchers to optimize firm value in a dynamic market environment.